Evidence for the charge asymmetry in pp → tt¯ $$ t\overline{t} $$ production at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Top Physics.; Springer Open.